Muscle strength and neuromuscular control of spine stability in low back pain: Elite athletes versus general population - Moreno Catalá, M.; Schroll, A.; Laube, G.; Arampatzis, A. (21st Annual Congress of the European College of Sport Science (ECSS), Vienna, 6. -9. July 2016, 2016)
Introduction: Chronic low back pain (LBP) is a worldwide-recognized problem with dramatic consequences for the quality of life of the affected patients. There is evidence that LBP patients show deficits in the neuromuscular control of the spine stability compared to healthy controls (Graham, 2014; Hodges, 2009). However, there is a lack of studies taking into account the specificity of LBP in competitive sports. Our purpose was to investigate the athletic-based specificity of neuromuscular differences between healthy and LBP individuals and to identify appropriate markers for the characterization and evaluation of LBP. Method: Two groups of athletes with (n=15) and without LBP (n=15) and two groups of non-athletes with (n=15) and without LBP (n=14) participated in the study. Muscle strength of the trunk was assessed during maximal isometric and isokinetic contractions using dynamometry. To quantify the neuromuscular control of trunk stability we examined trunk stiffness and damping as well as muscle response patterns using Quick Release experiments. Furthermore, we investigated the local dynamic stability of the spine using the maximum finite-time Lyapunov exponent ( max) under static and dynamic conditions. For the statistical analysis a two-way ANOVA was performed. Results The maximum isometric trunk extension moments were significantly lower in the LBP participants compared to healthy controls in both athletes and non-athletes. The analysis of interaction between condition (LBP) and groups showed that trunk stiffness was lower only in the non-athlete LBP participants. Trunk damping was significantly higher for the LBP participants in both groups. No significant differences were found in the muscle reaction times and in max between groups and conditions. Discussion Isometric muscle strength decrease of the trunk extensors is a LBP specific characteristic in athletes as well as in non-athletes. This provides evidence that this parameter is a suitable marker for the evaluation of LBP. Trunk stiffness is not sensitive enough to distinguish LBP participants from healthy controls in elite athletes, indicating an athleticbased specificity in the neuromuscular control of spine stability.